Mean Atlantic Meridional Overturning Circulation Across 26.5 degs N from Eddy-Resolving Simulations Compared to Observations - Xu, X; Schmitz, Jr, W J; Hurlburt, H E; Hogan, P J (2012)
Observations along 26.5 deg N are used to examine the time mean structure of the Atlantic meridional overturning circulation (AMOC) in eddy-resolving simulations with the Hybrid Coordinate Ocean Model (HYCOM). The model results yield a 5 year mean AMOC transport of 18.2 Sv, compared to 18.4 Sv based on data. The modeled northward limb of the AMOC has a vertical structure similar to observations. The southward limb is shallower than observed but deeper than other ocean general circulation models and includes a secondary transport maximum near 4000 m corresponding to Nordic Seas Overflow Water. The modeled flow through the Florida Strait and the deep western boundary current (DWBC) east of Abaco, Bahamas, are also approximately consistent with observations. The model results are used to clarify the sources of the northward AMOC transport and to explore the circulation pattern of the southward transport in the western subtropical North Atlantic in the range 18 33 N. About 14.1 Sv of the modeled northward AMOC transport is through the Florida Strait and the remainder through the mid-ocean, primarily in the Ekman layer, but also below 600 m. The modeled AMOC transport is about 2/3 surface water and 1/3 Antarctic Intermediate Water with no contribution from the thermocline water in between. In the western subtropical North Atlantic the model results depict a complicated deep circulation pattern, associated with the complex bathymetry. The DWBC flows southward then eastward in both the upper and lower North Atlantic Deep Water (NADW) layers but with different offshore recirculation pathways, and there exists a second, more northern branch of eastward flow in the lower NADW layer. Journal of Geophysical Research, v117 p1-17, 2012.